2003
DOI: 10.1073/pnas.1231792100
|View full text |Cite
|
Sign up to set email alerts
|

Alginate is not a significant component of the extracellular polysaccharide matrix of PA14 and PAO1Pseudomonas aeruginosabiofilms

Abstract: The bacterium Pseudomonas aeruginosa causes chronic respiratory infections in cystic fibrosis (CF) patients. Such infections are extremely difficult to control because the bacteria exhibit a biofilmmode of growth, rendering P. aeruginosa resistant to antibiotics and phagocytic cells. During the course of infection, P. aeruginosa usually undergoes a phenotypic switch to a mucoid colony, which is characterized by the overproduction of the exopolysaccharide alginate. Alginate overproduction has been implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
365
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(388 citation statements)
references
References 49 publications
19
365
3
1
Order By: Relevance
“…For FRD1 biofilms cultivated in the presence of added Ca 2ϩ in the medium, the relative abundances of the absorbance bands changed, with the alginate-associated bands becoming dominant. In particular, the band at 1,615 (carboxylate ion) increased and partially obscured the amide I (1,650) and amide was not a component of P. aeruginosa PAO1 biofilms (72). The FTIR spectra here verify those results.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…For FRD1 biofilms cultivated in the presence of added Ca 2ϩ in the medium, the relative abundances of the absorbance bands changed, with the alginate-associated bands becoming dominant. In particular, the band at 1,615 (carboxylate ion) increased and partially obscured the amide I (1,650) and amide was not a component of P. aeruginosa PAO1 biofilms (72). The FTIR spectra here verify those results.…”
Section: Resultssupporting
confidence: 80%
“…Similar results were obtained using a mutant derivative of the nonmucoid strain P. aeruginosa PAO1 engineered to overproduce alginate (25,60). On the other hand, results using wild-type P. aeruginosa PAO1 and PA14 showed that alginate was not associated with biofilms (72) and that a second polysaccharide likely encoded by a separate polysaccharide biosynthetic gene cluster may provide the extracellular matrix material for those cells (18,19,29). In another report, using P. aeruginosa PAO1, DNA was suggested to be the extracellular matrix material, since the addition of DNase to biofilms dispersed the bacteria (64).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The surface-dependent induction of algC expression correlated with stability of attachment, with cells that did not undergo algC upregulation demonstrating reduced ability to remain attached to the surface relative to that of cells with activated expression (33). While these findings suggested increased alginate production upon attachment, with alginate production contributing to biofilm resistance and being inversely linked to both flagellum-driven motility and twitching motility (48,139,165), it is now apparent that alginate is neither the major matrix polysaccharide nor required for biofilm development by nonmucoid P. aeruginosa strains, which are the first to colonize CF patients (121,144,167). Instead, recent chemical and genetic studies have demonstrated that the major polysaccharides produced by P. aeruginosa strains PAO1 and PA14 are Psl and Pel, with the roles of these two polysaccharides differing with respect to attachment and biofilm formation in a strain-specific manner.…”
Section: Figmentioning
confidence: 99%
“…A recent study describing the EPS of PAO1 biofilms identified the major carbohydrate moieties in this to include glucose, rhamnose, mannose, xylose, 3-deoxy-D-manno-oct-2-ulosonic acid (KDO),N-acetylgalactosamine, N-acetylfucosamine, and N-acetylglucosamine (70). More recently, two genetic loci (psl and pel) responsible for the production of mannose-rich (psl) and glucose-rich (pel) polymer components of P. aeruginosa EPS (18,19,52) were identified.…”
mentioning
confidence: 99%